3 ways to express 3 to the 5th power as the product of powers
First expression
=> 3 x 3 x 3 x 3 x 3 - In this expression, we multiplied 3 5 times and the product is 243
Second expression
=> 3 ^ 5, in where ^ read as raised to the power, the product is also 243
Third expression
=> 3^2 x 3^3
=> (3 x 3) x (3 x 3 x 3)
=> 9 x 27, the product also equals to 243.
recall in a perfect square trinomial, the middle term is the tale-tell guy, we know the middle term is the product of 2 and the two other guys without the exponent, so in this case 6x = 2*√x² * √c.
![\bf 6x=2\cdot \sqrt{x^2}\cdot \sqrt{c}\implies 6x=2\sqrt{x^2c}\implies 6x=2x\sqrt{c}\\\\\\\cfrac{6x}{2x}=\sqrt{c}\implies 3=\sqrt{c}\implies 3^2=c\implies 9=c](https://tex.z-dn.net/?f=%20%5Cbf%206x%3D2%5Ccdot%20%5Csqrt%7Bx%5E2%7D%5Ccdot%20%5Csqrt%7Bc%7D%5Cimplies%206x%3D2%5Csqrt%7Bx%5E2c%7D%5Cimplies%206x%3D2x%5Csqrt%7Bc%7D%5C%5C%5C%5C%5C%5C%5Ccfrac%7B6x%7D%7B2x%7D%3D%5Csqrt%7Bc%7D%5Cimplies%203%3D%5Csqrt%7Bc%7D%5Cimplies%203%5E2%3Dc%5Cimplies%209%3Dc%20)
Answer:
y = 3x
Step-by-step explanation:
:)
:)
:)
Hope this helps!
-Josh
Answer:
The answer is 5/8
Step-by-step explanation:
Step 1 : Convert both fractions so they have the same denominator (bottom number in the fraction.)
1/4 = 2/8
So now were dealing with :
2/8 + 3/8 = ?
Step 2 : Add the numerators together to get the numerator for our answer.
2 + 3 = 5
When adding two fractions with the same denominator the denominator stays the same, so our answer is 5/8.
Hope this helps, please mark brainliest. :) Have a nice day.